MAGIC: A Collaboration Project to Globally Connect Researchers and Academics - De Oliveira Guimarães, Leandro Marcos; López, María José (My University, 2015)
Building on the success of the ELCIRA project, RedCLARA - with partners from Latin America, Europe, the Caribbean, West and Central Africa, Eastern and Southern Africa, North Africa and the Middle East, Central Asia and Asia-Pacific is leading MAGIC (Middleware for collaborative Applications and Global vIrtual Communities), a cooperation project that aims to significantly improve the ability of researchers and academics around the world to collaborate together. MAGIC might be the first really global collaborative project in the REN environment. But which are the benefits of the project to its partner institutions’ (UbuntuNet and WACREN) members? How can the African researchers and academics benefit from MAGIC? By fostering and easing collaboration and mobility, MAGIC is fostering intra-regional and global collaboration, helping to reduce the technological gap, and as a consequence, in the long term, to reduce the brain drain.
Keywords: Collaboration; identity federations; eduroam; eduGAIN; scientific communities; researchers; academics; RENs; NRENs